Maternal Employment and Gender Role Attitudes: Dissonance Among British Men and Women in the Transition to Parenthood - Pia Schober; Jacqueline Scott (Work, Employment & Society, 2012)
This study examines how changes in gender role attitudes of couples after childbirth relate to women's paid work and the type of childcare used. Identifying attitude-practice dissonances matters because how they get resolved influences mothers' future employment. Previous research examined changes in women's attitudes and employment, or spouses' adaptations to each others' attitudes. This is extended by considering how women and men in couples simultaneously adapt to parenthood in terms of attitude and behavioural changes and by exploring indirect effects of economic constraints. Structural equation models and regression analysis based on the British Household Panel Survey (1991-2007) are applied. The results suggest that less traditional attitudes among women and men are more likely in couples where women's postnatal labour market participation and the use of formal childcare contradict their traditional prenatal attitudes. Women's prenatal earnings have an indirect effect on attitude change of both partners through incentives for maternal employment.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Britain; childcare; cognitive dissonance; female employment; gender role attributes; parenthood